Neuro-Glia-Vascular-on-a-Chip System to Assess Aggravated Neurodegeneration via Brain Endothelial Cells upon Exposure to Diesel Exhaust Particles - Seo Su Yeong; Jang, Minjeong; Kim, Hwieun; Sung, Jong Hwan; Choi, Nakwon; Lee, Kangwon; Kim, Hong Nam (John Wiley & Sons Ltd., 2023)
Air pollution induces neurodegeneration, including cognitive deficits, neuroinflammation, and disruption of the blood-brain barrier. The mechanisms underlying air pollution-mediated neurodegeneration have not yet been fully elucidated given the limited knowledge on intercellular interactions. A brain-on-a-chip platform is presented comprising neurons, glia, and brain endothelial cells (bECs; neuro-glia-vascular, NGV) and diesel exhaust particle (DEP)-induced neurodegeneration is evaluated with a particular focus on the intercellular interactions. DEP exposure in the NGV model yields Alzheimer's disease-like signatures, including amyloid beta accumulation, tau phosphorylation, hydrogen peroxide (H2O2)/reactive oxygen species (ROS) production, and neuronal cell death. bEC-secreted granulocyte-macrophage colony-stimulating factor (GM-CSF) stimulates microglial activation and the overproduction of H2O2/ROS in microglia, suggesting that the bEC-microglia-neuron is a neurodegeneration cascade. Pharmacological inhibition at each step of the cascade, including GM-CSF neutralization, microglial activation suppression, and ROS scavenging, prohibits neurodegeneration in the NGV model. Therefore, intercellular interactions should be further studied of air pollution-induced neurodegeneration.